MADV-DAQ: Multi-channel Arduino-based differential voltage data acquisition system for remote strain measurement applications. (October 2022) - Louw, Hendrik; Broekman, André; Kearsley, Elsabé
Graphical abstract: Highlights: Successful open-source hardware integration for monitoring wind turbines. Remote strain measurements and monitoring of soil-structure interaction. Remote data acquisition using existing cloud-based data platforms. Low-cost alternative for general purpose differential voltage measurements. Abstract: Wind turbine power generation, both onshore and offshore, has gained significant popularity over the past few decades. However, the design of a turbine's foundation, capable of supporting a tall structure subject to large horizontal forces, remains challenging. Complex wind loading and intricate soil-structure interaction between the foundation and the supporting soil requires consideration. Although commercial structural health monitoring (SHM) systems provide several advantages, they remain cost prohibitive. This paper demonstrates the development, testing, fabrication, installation and validation of a low-cost, multi-channel, Arduino-based differential voltage data acquisition system (MADV-DAQ) suitable for remote, battery powered measurements of multiple Wheatstone bridge-based (strain) sensors. The instrumented wind turbine (120 m high, 3.45 MW generation capacity) forms part of a newly constructed onshore wind farm in South Africa. The developed MADV-DAQ system proved valuable in measuring strains associated with the wind turbine tower, quantifying the true magnitude of the loads being transferred to the underlying foundation. MADV-DAQ was designed to relay the real-time measurements to two, independent cloud platforms for aggregation, visualization and subsequent analysis. MADV-DAQ was purposefully designed as a universal data acquisition system, compatible with any Wheatstone bridge-based sensor design, including strain gauges, tensiometer and similar MEMS-based sensors.